2020
DOI: 10.1080/09602011.2020.1774397
|View full text |Cite
|
Sign up to set email alerts
|

Goal adjustment by people living with long-term conditions: A scoping review of literature published from January 2007 to June 2018.

Abstract: Long-term health conditions can limit achievement of personal goals. We aimed to map and synthesize definitions of goal adjustment, theoretical underpinnings, associations with recovery and supportive interventions for adults with long-term conditions. We searched multiple databases (January 2007-June 2018) and identified peer-reviewed research relating to goal adjustment. Data were charted, mapped and synthesized using content analysis and descriptive summaries. Two stakeholder consultations informed the revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 112 publications
(174 reference statements)
1
3
0
Order By: Relevance
“…The finding that goal reengagement explained a unique proportion of the variance of both indicators of QOL corrobates the conclusions of earlier research with people with an ABI ( Van Bost, Van Damme & Crombez, 2020 ). It is also in concordance with an overall positive relationship between goal reengagement and well-being in long-term health conditions, reported by Scobbie et al (2020) . In their review mixed results for goal disengagement were reported.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The finding that goal reengagement explained a unique proportion of the variance of both indicators of QOL corrobates the conclusions of earlier research with people with an ABI ( Van Bost, Van Damme & Crombez, 2020 ). It is also in concordance with an overall positive relationship between goal reengagement and well-being in long-term health conditions, reported by Scobbie et al (2020) . In their review mixed results for goal disengagement were reported.…”
Section: Discussionsupporting
confidence: 86%
“…Similar results have been found in people with an ABI ( Van Bost, Van Damme & Crombez, 2020 ). In their review of the literature concerning goal adjustment in people with long-tern health conditions, such as cancer and stroke, Scobbie et al (2020) concluded that goal disengagement and goal reengagement had a positive association with recovery and well-being, although the findings for goal disengagement were mixed. In clinical studies ( Van Bost, Van Damme & Crombez, 2020 ; Van Damme et al, 2019 ) goal reengagement was positively associated with subjective QOL and life satisfaction.…”
Section: Introductionmentioning
confidence: 99%
“…Individuals faced with the decision of whether to continue pursuing a failing course of action are more likely to question the value of continued pursuit and downgrade goal-relevant resources (Herrmann et al, 2019). Accepting a goal's unattainability, unburdening resources, and ultimately disengaging from a failing goal enables goal adjustment (i.e., modifying a goal to make it achievable; Barlow et al, 2020; Brandstätter & Bernecker, 2022; Carver & Scheier, 2005; Scobbie et al, 2021; Wrosch & Scheier, 2020). Although controlled motivation is positively associated with disengagement, it is not predictive of adjustment (Ntoumanis, Healy, Sedikides, Duda, et al, 2014; Ntoumanis, Healy, Sedikides, Smith, & Duda, 2014).…”
Section: The Role Of Motives In Self-regulatory Copingmentioning
confidence: 99%
“…37 Research has described coping strategies associated with long-term disabling conditions and suggests therapies, such as increasing a person's empowerment or self-management skills and using peer support. Goal adjustment has been described in people with long-term conditions, 80 including cancers. 81 This theory suggests research is needed to assist people to adapt their long-term aspirations, accounting for their altered abilities.…”
Section: Resetting Psychosocial Equilibrium Set Pointsmentioning
confidence: 99%